2010
DOI: 10.1016/j.cellimm.2010.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Elevated neutrophil respiratory burst activity in essential hypertensive patients

Abstract: Neutrophils play a significant role in maintaining the integrity of innate immunity via their potent respiratory burst activity. However, the uncontrolled activation of respiratory burst in neutrophils also attributes to chronic diseases such as primary hypertension and atherosclerosis. In our study, we have investigated the activation of respiratory burst function of neutrophils harvested from essential hypertensive patients. In the presence of stimuli PMA and opsonized zymosan (OZ), hypertensive patients' ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…A close relationship has been demonstrated between a high PMN count and increased cardiovascular risk (Horne et al 2005), and patients with unstable angina or acute myocardial infarction moreover present activated PMNs that release free oxygen radicals and inflammatory mediators which in turn interact with the endothelial cells-triggering the development of atherosclerosis (Baetta and Corsini 2010). Furthermore, circulating PMNs have been shown to be activated in a number of conditions associated with a high risk of developing atherosclerosis, such as hypertension (Ramasamy et al 2010), type 2 diabetes (Hand et al 2007), or hyperlipidemia (Mazor et al 2008). The causal role of PMNs in atherogenesis and their implication in plaque vulnerability ) are presently widely accepted.…”
Section: Discussionmentioning
confidence: 99%
“…A close relationship has been demonstrated between a high PMN count and increased cardiovascular risk (Horne et al 2005), and patients with unstable angina or acute myocardial infarction moreover present activated PMNs that release free oxygen radicals and inflammatory mediators which in turn interact with the endothelial cells-triggering the development of atherosclerosis (Baetta and Corsini 2010). Furthermore, circulating PMNs have been shown to be activated in a number of conditions associated with a high risk of developing atherosclerosis, such as hypertension (Ramasamy et al 2010), type 2 diabetes (Hand et al 2007), or hyperlipidemia (Mazor et al 2008). The causal role of PMNs in atherogenesis and their implication in plaque vulnerability ) are presently widely accepted.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress in hypertensive patients' neutrophils is evidenced by an increased NADPH oxidase production and lipid peroxidation and decreased cytosolic and mitochondrial superoxide dismutase concentration 42,43,44,45. Recently, Ramasamy et al46 evaluated the effect of neutrophil oxidative burst activity in essential hypertensive patients. They found that freshly isolated neutrophils from uncontrolled human subjects diagnosed with essential hypertension acquire the ability of producing a higher amount of ROS in response to stimuli indicating that oxidative bust activity is impaired.…”
Section: Discussionmentioning
confidence: 99%
“…Supernatant from dextran sedimentation was collected and centrifuged at 1800 rev./min for 10 min at room temperature. The remnant RBC was lysed using hypotonic lysing procedure to obtain the pure PMN population (Ramasamy et al, 2010). The morphological examination and cell count were performed to determine the cell count and purity of the PMN.…”
Section: Methodsmentioning
confidence: 99%